Python v kemiji in kemijskem inženirstvu: Učbenik za predmet Računalništvo v kemiji - Novak Pintarič, Zorka; Potrč, Sanja; Bogataj, Miloš (University of Maribor Press, 2025)
Python in Chemistry and Chemical Engineering: Textbook for the Course Computer Science in Chemistry. The textbook Python in Chemistry and Chemical Engineering is intended for first-year students who are new to computer programming. It provides a clear and systematic introduction to the fundamentals of the Python programming environment and gradually demonstrates its application in solving selected problems from chemistry and chemical engineering. In addition to the basics, it introduces students to modern digital approaches such as data analysis and artificial intelligence, offering insight into current trends in the chemical engineering profession. The textbook is organized to build practical computational skills, promote independent learning, and encourage further exploration. Published as open educational material, it offers lasting support for students, educators, and professionals interested in applying Python in chemistry and chemical engineering.